2016
DOI: 10.1007/s40817-016-0013-0
|View full text |Cite
|
Sign up to set email alerts
|

Latent Dimensions of Executive Functions in Early Childhood

Abstract: Executive functions (EF) are known to be a multidimensional construct in adults; however, the underlying dimensions of EF in early childhood are unclear. Theoretical models of EF have generally suggested the importance of language, attention, and inhibition abilities as developmental foundations for EF abilities. This study investigated the construct validity of EF by administering a diverse battery of measures of EF along with cognitive measures representing different theoretical models of EF (language, atten… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
3
0
2

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 12 publications
(5 citation statements)
references
References 62 publications
0
3
0
2
Order By: Relevance
“…It is known that the level of sustainability of attention is the basis for academic success (Clark, Pritchard, & Woodward, 2010). It is also believed that sustained attention is an essential part of executive functions, along with verbal abilities and behavioral control (Decker, Ezrine, & Ferraracci, 2016). Interestingly, in our previous studies, which aimed to identify predictive markers for four-and five-year-olds (Nasledov et al, 2018), this factor was not found.…”
Section: Discussionmentioning
confidence: 80%
“…It is known that the level of sustainability of attention is the basis for academic success (Clark, Pritchard, & Woodward, 2010). It is also believed that sustained attention is an essential part of executive functions, along with verbal abilities and behavioral control (Decker, Ezrine, & Ferraracci, 2016). Interestingly, in our previous studies, which aimed to identify predictive markers for four-and five-year-olds (Nasledov et al, 2018), this factor was not found.…”
Section: Discussionmentioning
confidence: 80%
“…Likewise, the development of the child's attention must be determined in each stage of life with greater specification. Attention, object permanence, and tool use, while not part of the same construct, are precursors to the development of EFs and can be observed at very early ages (Decker et al, 2016;Pauen & Bechtel-Kuehne, 2016). Additionally, temperament, similar to EFs, predicts inhibition outcomes.…”
Section: Discussionmentioning
confidence: 99%
“…Известно, что уровень произвольности внимания лежит в основе академической успешности [Clark et al, 2010]. Также считается, про произвольное внимание входит в состав исполнительных функций наряду с вербальными способностями и поведенческим контролем [Decker et al, 2016]. Интересно, что в наших предшествовавших исследованиях по выявлению прогнозных маркеров для четырех-и пятилетних детей [Наследов и др., 2018b, 2018c], этот фактор не обнаружился.…”
Section: Discussionunclassified